2022
DOI: 10.1265/ehpm.22-00085
|View full text |Cite
|
Sign up to set email alerts
|

The Lifelong Health Support 10: a Japanese prescription for a long and healthy life

Abstract: Background Although the age-adjusted incidence and mortality of cancer and cardiovascular disease (CVD) have been decreasing steadily in Japan, both diseases remain major contributors to morbidity and mortality along with the aging society. Herein, we aim to provide a prescription of 10 health tips for long and healthy life named the “Lifelong Health Support 10 (LHS10).” Method The LHS10 was developed by the preventive medicine specialists at the National Cerebral and C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 161 publications
0
17
0
Order By: Relevance
“…31, 32 Avoiding smoking is a substantial factor in the Lifelong Health Support 10 (LHS10) scheme proposed by the preventive medicine specialists at the NCVC, based on Japanese epidemiological evidence, to prevent CVD, including AF. 33 Notably, the spline curves (Figure ) showed that the linear association between WBC count and AF risk was significantly more prominent among those with WBC levels <3.1 or >8.4×10 9 /L. The Japan Society of Ningen Dock suggested a WBC count between 3.1 and 8.4×10 9 /L as a reference range.…”
Section: Discussionmentioning
confidence: 96%
“…31, 32 Avoiding smoking is a substantial factor in the Lifelong Health Support 10 (LHS10) scheme proposed by the preventive medicine specialists at the NCVC, based on Japanese epidemiological evidence, to prevent CVD, including AF. 33 Notably, the spline curves (Figure ) showed that the linear association between WBC count and AF risk was significantly more prominent among those with WBC levels <3.1 or >8.4×10 9 /L. The Japan Society of Ningen Dock suggested a WBC count between 3.1 and 8.4×10 9 /L as a reference range.…”
Section: Discussionmentioning
confidence: 96%
“…Based on previous literature about HF and CVD risk factors, 29,30 we included the following baseline covariates in the Cox regression models: age (continuous), BMI (<18.5, 18.5-24.9, and ≥25.0 kg/m 2 ), smoking (never, former, or current), alcohol drinking (never, former, moderate [<46 g ethanol/d], or excessive [≥46 g ethanol/d]), hypertension defined as systolic/diastolic blood pressure of 140/90 mm Hg or greater or hypertension medication (yes or no), diabetes defined as fasting blood glucose of 126 mg/dL or greater or diabetes medication (yes or no), cardiac murmurs or valvular disease assessed clinically or using medical records (yes or no), arrhythmia including atrial fibrillation documented by baseline electrocardiogram or medical records (yes or no), history of CVD (stroke and/or ischemic heart disease) (yes or no), chronic kidney disease (CKD) defined as estimated glomerular filtration rate less than 60 mL/min per 1.73 m 2 (yes or no), and lipid-lowering agent use (yes or no). We further adjusted for baseline BNP pg/mL (continuous) and TC (<160, 160-199, 200-239, and ≥240 mg/dL) in separate models.…”
Section: Discussionmentioning
confidence: 99%
“…Cardiovascular disease (CVD) continues to stand as the primary contributor to morbidity and mortality both in Japan and worldwide [ 1 ]. Yet, the effective management of modifiable risk factors associated with CVD could play a pivotal role in alleviating its burden [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Given that 1) modifying CVD risk factors is essential for CVD prevention [ 2 , 3 ], 2) stair climbing is a sort of physical activity with potential health merits [ 4 8 ], 3) studies investigating the association between stair climbing and modifiable CVD risk factors are scarce with inconsistent results [ 4 8 ], and 4) relevant findings from Asian populations are lacking, we performed this study to investigate the association between stair climbing and several modifiable CVD risk factors in a Japanese sample.…”
Section: Introductionmentioning
confidence: 99%